Mercosur marriage. - BLOUNT, Jeb (1996)
Asserts that from a collection of four largely closed and ailing economies, Mercosur members have transformed themselves into a single market of 206 million consumers trading mostly freely across once-difficult borders and generating an annual GDP of US